Rheumatoid arthritis subtypes identified by genomic profiling of peripheral blood cells: assignment of a type I interferon signature in a subpopulation of patients. Issue 8 (12th January 2007) - van der Pouw Kraan, T C T M; Wijbrandts, C A; van Baarsen, L G M; Voskuyl, A E; Rustenburg, F; Baggen, J M; Ibrahim, S M; Fero, M; Dijkmans, B A C; Tak, P P; Verweij, C L
Abstract : Background: Rheumatoid arthritis (RA) is a heterogeneous disease with unknown cause. Aim: To identify peripheral blood (PB) gene expression profiles that may distinguish RA subtypes. Methods: Large-scale expression profiling by cDNA microarrays was performed on PB from 35 patients and 15 healthy individuals. Differential gene expression was analysed by significance analysis of microarrays (SAM), followed by gene ontology analysis of the significant genes. Gene set enrichment analysis was applied to identify pathways relevant to disease. Results: A substantially raised expression of a spectrum of genes involved in immune defence was found in the PB of patients with RA compared with healthy individuals. SAM analysis revealed a highly significant elevated expression of interferon (IFN) type I regulated genes in patients with RA compared with healthy individuals, which was confirmed by gene ontology and pathway analysis, suggesting that this pathway was activated systemically in RA. A quantitative analysis revealed that increased expression of IFN-response genes was characteristic of approximately half of the patients (IFN high patients). Application of pathway analysis revealed that the IFN high group was largely different from the controls, with evidence for upregulated pathways involved in coagulation and complement cascades, and fatty acid metabolism, while the IFN low group was similar to the controls. Conclusion: The IFN type I signature defines a subgroup of patients with RA, with a distinct biomolecular phenotype, characterised by increased activity of the innate defence system, coagulation and complement cascades, and fatty acid metabolism.